Screening varices in patients with HBV‐related cirrhosis on antiviral therapy: Platelet alone or together with LSM. (18th December 2020) - Wang, Bingqiong; Zhou, Jialing; Wu, Xiaoning; Sun, Yameng; Li, Lei; Li, Ping; Li, Minghui; Jiang, Wei; Xu, Mingyi; Feng, Bo; Xu, Xiaoyuan; Cheng, Jilin; et al.
Abstract: Background & Aims: Non‐invasive assessment criteria to rule out high‐risk varices (HRV) in compensated hepatitis B virus (HBV) cirrhosis on antiviral therapy remains unclear. Methods: HBV‐related compensated cirrhotic patients who underwent screening endoscopy during antiviral therapy were enrolled and randomly divided into the derivation and validation sets. HRV were defined as medium to large varices or small varices with red signs. Univariate and multivariate logistic analysis were used to determine the parameters associated with HRV. Results: A total of 436 HBV‐related compensated cirrhotic patients screened for varices were enrolled, the median duration of antiviral therapy was 4 years (IQR: 2.5‐5.5 years). In the derivation set (N = 290, 17.2% with HRV), only platelet (PLT) count (OR = 0.972, 95% CI 0.961‐0.984, P < .05) was independently associated with HRV, whereas liver stiffness measurement was not associated with the presence of HRV. With a PLT count cut‐off value of 105 × 10 9 /L, unnecessary endoscopies could be spared in 56.9% patients, with a 3.6%. risk of missing HRV. In the validation cohort (N = 146, 16.4% with HRV), the proportion of patients that could safely spare endoscopies (61.0%) identified by this PLT count cut‐off value was higher than that obtained by using Baveno VI criteria (34.9%), with an acceptable risk of missing HRV (3.4%). Conclusion: Compared with the 'Baveno VI criteria or beyond' criteria, PLT count higher than 105 × 10 9 /L could safely spare more screening endoscopies without increasing the risk of missing HRV in patients with HBV‐related compensated cirrhosis on antiviral therapy.